The double-edged sword effect of resilient leadership on the followership of hotel employees - Cui, Hanghang; Wang, Xiaoling (Transformations In Business & Economics, 2026)
Amid heightened volatility in the global tourism industry and escalating market uncertainty, the operational stability and service quality of the hotel sector depend on the efficiency of leader-member exchange. Resilient leadership emerges as a critical leadership style for navigating adversity, with employee followership determining the depth and responsiveness of interaction. However, the mechanism through which resilient leadership influences employee followership remains unexplored. To address this theoretical gap, drawing on the Job Demands–Resources model and the Conservation of Resources, using a multi-wave survey of 578 hotel employees, the double-edged sword effect of resilient leadership on employee followership, its underlying mechanisms, and boundary conditions were examined. Results show that (1) resilient leadership is significantly and positively correlated with both positive and negative followership; (2) employee cognitive reappraisal and ego depletion mediate these relationship between resilient leadership and positive versus negative followership; and (3) environmental uncertainty negatively moderates the relationship between resilient leadership and ego depletion, meaning higher environmental uncertainty weakens the effect of resilient leadership on ego depletion. The conclusions enrich research on the relationship between resilient leadership and followership, providing theoretical foundations and practical insights for the hospitality industry to effectively leverage the positive effects of resilient leadership while mitigating its negative impact.
Keywords: resilient leadership; positive followership; negative followership; cognitive reappraisal; ego depletion